The reputation of young Muslims in Italy in the platform society. Towards overcoming stereotypes and a recovery of religious identity - Crescenti, Martina; Lippolis, Martina (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
This article analyses the ways in which the second generation of young Italian Muslims re-establish their reputation, both in physical and digital spaces, in relation to their religious identity, which is associated by part of society with false stereotypes of religious fanaticism, terrorism and misogyny.